Advance Care Planning in the Time of COVID: Real-World Case Discussions. (17th December 2021) - Frechman, Erica; Buck, Harleah
Abstract: COVID has accelerated the science and practice of palliative care while creating a sense of urgency in advance care planning (ACP). Past palliative care principles and practices have been stressed to the breaking point, causing the need for new ACP approaches to elicit patient-and-family goals/values/preferences. In this presentation, two cases will be used to discuss pragmatic implications and real-world implementation strategies in the trenches of the major health care system disruptor of this generation. We will discuss access to documentation, immediacy and complexity of the decision-making process, provider impacts, role of the family, and even an upside to this crisis. This will include questions of ethics and equity. The first case involves an older man whose family disregarded his wishes, while the second case discusses the pitfalls and pearls when family cannot visit. These two cases highlight COVID's impact on ACP and cause us to re-think its process and delivery.